Rehabilitation of the upper extremity and basic activities of daily living in the first month after ischemic stroke: an international cohort comparison study - Cesar Minelli; Francisco A.A. Gondim; Amilton Antunes Barreira; Alexander W. Dromerick (MDPI AG, 2009)
Background: Inpatient rehabilitation has been traditionally employed in developed countries, while in developing countries, outpatient rehabilitation is the rule. The purpose of this study was to compare the patterns of recovery of upper extremity (UE) function, global impairment and independence in activities of daily living (ADL) during the first month after ischaemic stroke in inpatient (United States) and outpatient (Brazil) rehabilitation settings. Design and Methods: This is a prospective cohort comparison study. Twenty patients from each country were selected using identical inclusion criteria. The study measures employed were the UE portion of the Fugl-Meyer scale, the Action Research Arm test, the National Institutes of Health Stroke Scale and Barthel Index. Changes from baseline to the end of treatment, efficiency and effectiveness of each treatment were compared. Results: Both populations exhibited significant improvement between the first and second evaluations in the four outcome scales (P 0.05). Conclusions: Substantially different treatment approaches after ischaemic stroke led to similar results in UE function, global impairment and ADL. Further studies in larger populations should be performed in order to confirm the present results.